2020
DOI: 10.1007/s10916-020-01570-1
|View full text |Cite
|
Sign up to set email alerts
|

Causation between Pathway Completion and Reduced Hospital Stay in Patients with Lung Cancer: a Retrospective Cohort Study Using Propensity Score Matching

Abstract: We have previously demonstrated that clinical pathway completion helps reduce hospital stays. However, our previous results showed only a correlation, not causation. Therefore, the current study's aim was to analyze the causation between clinical pathway completion and reduced hospital stays for patients with lung cancer. Data were collected from April 2013 to March 2018 from the electronic medical records of the University of Miyazaki Hospital. We used propensity score matching to extract records from 227 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Second, the method employs LHS as an exposure time of treatment risk in medicine but not an efficiency indicator. Although various research articles [45][46][47][48][49] have demonstrated the importance of decreasing LHS, the present study has discussed LHS from different perspectives. Finally, the practice of attaching too much importance to decreasing LHS is criticized herein because of the social health insurance system in Japanese acute medical organizations called the Diagnosis Procedure Combination (DPC) payment system.…”
Section: Significancementioning
confidence: 87%
“…Second, the method employs LHS as an exposure time of treatment risk in medicine but not an efficiency indicator. Although various research articles [45][46][47][48][49] have demonstrated the importance of decreasing LHS, the present study has discussed LHS from different perspectives. Finally, the practice of attaching too much importance to decreasing LHS is criticized herein because of the social health insurance system in Japanese acute medical organizations called the Diagnosis Procedure Combination (DPC) payment system.…”
Section: Significancementioning
confidence: 87%